Atypical Mongolian spots in an infant: A harbinger of lysosomal storage disorders - Manisha Varma Gadhiraju; Navya Sree Manugu; Sangeetha Etikela; Yerroju Kodandapani (Wolters Kluwer Medknow Publications, 2021)
Background: Atypical Mongolian spots are lesions that are aberrant in location (over the abdomen, back, legs, shoulders, or arms), extensive in distribution, persist beyond early infancy, and/or progressively increase in number. These are frequently associated with lysosomal storage disorders or neurocristopathies. Clinical Description: A 4-month-old girl presented with a common cold. Extensive aberrant Mongolian spots over the back, buttocks, lower limbs, and new onset grayish-blue macular spots over the abdomen prompted us to do a detailed evaluation to look for any underlying pathology. Other salient clinical findings included coarse facies, hepatomegaly, absence of significant developmental delay, bilateral macular cherry red spots, and ovoid-shaped vertebral bodies. The clinical phenotype was that of a lysosomal storage disorder possibly GM1 gangliosidosis. This was confirmed by deficient levels of ß-galactosidase. Management: The parents underwent genetic counseling. The infant was enrolled in an early intervention program. By the age of 6 months, the infant had not acquired any new developmental skills and new Mongolian spots did not develop. Subsequently, the family was lost to follow-up. Conclusion: Infants with aberrant Mongolian spots need to undergo an in-depth evaluation to identify underlying systemic disorders, even if they are asymptomatic. Diagnosis helps in providing supportive care to the child, specific therapy (if available) and the option of prenatal diagnosis in subsequent pregnancies.